A identidade no discurso pedagógico: o embate de vozes e lugares sociais - Martins, Débora Sousa (2014)
The thesis Identity in pedagogic discourse: the conflict of voices and social places aims to interpret and analyze the interplay of voices cleaved by various discursive and ideological formations of the subject throughout its history, the construction of the identity of the subject / teacher of Portuguese. And specific objectives, describing a regular speech, learning the meanings that derive from there in order to understand the conception that the subject / teacher Portuguese have of themselves and their teaching throughout his career, glimpsing thus their movements identification with different discursive formations. This is a case study conducted with eight teachers of basic education, and, four of the secondary school and four from high school, all public schools Jataí / GO. Thus, there were eight collaborators, four in one school and another four, and all enabled in Portuguese lyrics. To discuss the theme of identity have as main theoretical Bauman (2005), Silva (2003) and especially Hall (2003a, 2001, 2003b, 2003c). This concept here is related to teacher education Portuguese. In this case, the theoretical considerations are made also anchored in ideas Perrenoud (2001), Tardif (2002), Nóvoa (1995), Pepper (2005), Brzezinski (2002). Therefore, it is a qualitative research Denzin and Lincoln (2006), I adopt the theoretical and methodological devices Analysis of Discourse -centered discourse analyzes developed by Pêcheux (1990, 1997, 1998, and 1999) as input for gesture interpretation released on the corpus. Still use the concepts of Maingueneau (2004, 2008) on the concept of ethos. I depart of the thesis that also in the process of identity construction works gesture interpretation of the subject that affected the historicity and ideology, recovers in interdiscourse, some statements and not others to incorporate into your speech. So that the speech and the subject are characterized by heterogeneity, by contradiction, we investigate the clash of voices in the discursive construction of images of themselves, the profession - teaching of Portuguese language and its object of study - the language underlying the apparent linearity speech of the research subjects. The corpus consists of interviews of the subjects studied, which were obtained through written questionnaires and semi-structured interviews. I have confirmed that the subjects studied his sayings are situated in a hybrid territory, from which the images themselves, the object of study and profession are discursively constructed. And the identity of these individuals is not fixed but fluid, mobile, thus re (construes) constantly. Therefore, the constructed images are not set apart from the very condition of the subject teacher as this, when speaking of the profession and language also speaks of himself, revealing the incompleteness that constitute him.